Quality of Abdominal Surgical Nursing Care - Istomina, Natalja (Annales Universitatis Turkuensis D 987, 2011)
The study evaluates the quality of abdominal surgical nursing care. The data were collected from patients (n=1208) having undergone abdominal surgical operations on their last day of hospitalization and nurses (n=218) working in the same wards. Three instruments originally created in Finland and adapted to the Lithuanian context were used: (1) Good Nursing Care Scale for patients and nurses (GNCS-P, GNCS-N), (2) Nurse Competence Scale (NCS), and (3) Nurse Empowerment Scale (NES). Patient and nurses’ perceptions of the quality of nursing care were evaluated. In addition, nurses’ perceptions of their competence and empowerment were evaluated. The patient and nurses' perceptions of the quality of abdominal surgical nursing care were positive, with more criticism in the nurses’ perceptions. Both patients and nurses gave the lowest evaluation to the quality in the progress of nursing care and the co-operation with significant others. The nurses gave the highest evaluation to the self-assessed level of their competence and the frequency of using competences in practice, with the highest assessment given to situation management and their role at work and the lowest to teaching-coaching and ensuring quality. The nurse perceptions of their empowerment were positive in the qualities and performance of an empowered nurse and empowerment promoting factors, with the highest evaluation in moral principles and sociability and the lowest evaluation in the future-orientedness and expertise. The empowerment-impeding factors were evaluated as negative. The perceptions of the quality of nursing care of both patients and nurses had significant correlations with patient and nurse satisfaction and nurse job independence. The nurse perceptions of their competence and empowerment correlated with their education, the type of the nurse license, completed courses of development of their knowledge and skills, nurse job independence, and nurse satisfaction. The nurse perceptions of the quality of nursing care had a positive correlation with their perceptions of competence and empowerment. Generally, the quality of nursing care was evaluated as high and had correlations with the patients' demographic and satisfaction factors and with the nurse demographic, work-related, and satisfaction factors. The study produced the knowledge that the quality in co-operation with significant others and the progress of nursing process, surgical nurse competence in teaching-coaching, and future-orientedness of surgical nurse empowerment need to be improved in order to develop the quality of abdominal surgical nursing care. The knowledge may be used to offer better services for abdominal surgical patients and increase their satisfaction with nursing care, as well as to increase nurses' satisfaction with work and independence at work. The study suggests implications for clinical practice and management, nursing education, and nursing research.